Operative management of idiophatic myositis ossificans of lateral pterygoid muscle - Almeida, Luis Eduardo (Int J Surg Case Rep, 2014)
INTRODUCTION: Myositis ossificans (MO) is characterized as heterotopic bone formation within muscle. MO rarely occurs in the head and neck region. Excision of the heterotopic bone is the standard treatment. This report summarizes a case of a 12-year old female with MO involving the lateral pterygoid muscle. The heterotopic bone was excised using an intraoral incision. Despite intensive physical therapy, the operation failed as evidenced by new bone formation in the area within three weeks of the operation. PRESENTATION OF CASE: A twelve years old female patient presenting with mouth opening of 10 mm, no facial asymmetry, and no jaw joint pain or other symptoms. Computer tomography (CT) exam was requested and revealed calcification of the left lateral pterygoid muscle. No other masticatory or head muscles showed any signs of calcification. The calcified muscle was completely removed beyond the ossified segment and a 35 mm mouth opening was achieved immediately after the procedure. One month after total bone structure removal (first surgery) the patient could not open her mouth anymore due to a significant calcified mass. DISCUSSION: The surgical technique used in this case avoided invasive gap arthroplasty to access lateral pterygoid muscle and anaesthetic scarring formation, by using an intraorally incision accessing the muscle directly. The authors of these study did not see any relation with the condylar dislocation that the patient had five years prior to the pathology, and they could not find any real cause for the myositis ossificans of lateral pterygoid muscle. CONCLUSION: The outcome of the surgical procedure was not successful, perhaps due to the expression of the disease, indicating the need to further physiologic and genetic studies to elucidate the aetiology of MO as well as to provide directions to an adequate treatment choice for such cases.